Hiperanálise: a estrutura hipermidiática da construção do conhecimento - Santos, Rogerio Cardoso dos (2009)
This research work presents a conceptual proposal of hyperanalysis, due to the act of hypermedia construction. The hyperanalysis is conceptualized as the thought hypermedia conceptualized as to analysis using the hypermedia language and includes a thought of using the sounds, images, text and interactivity. Far from the creation of a hypermedia being the digital version of various media, including in it the text, it is actually the exercise of a type of thinking that no longer is based only on verbal, with its own structure of a network emerge that significant. This structure is the programming environment, which in many ways is not neutral but has a strong meaning in itself, as well as any non-linear narratives that can be part of the route of the reader